2009
DOI: 10.1186/cc7684
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant properties of drotrecogin alfa (activated) during hemofiltration in patients with severe sepsis

Abstract: In a retrospective study among 35 severely septic patients treated with drotrecogin alfa (activated) (DrotAA) and renal replacement therapy (RRT), Camporota and colleagues demonstrated that the addition of heparin, epoprostenol, or both to DrotAA during RRT did not improve filter survival. Furthermore, in a multivariate logistic regression analysis, they identified the minimum value in platelet count as the only predictive factor of filter clotting during DrotAA infusion. These findings are in line with the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The antioxidative activity of carnosine and 16 related compounds, both synthetic and natural, has been determined [ 15 18 ]. Antioxidative effects were estimated by the ability of the dipeptides to prevent MDA accumulation over the course of lipid peroxidation (LPO) induced in rabbit sarcoplasmic reticulum membranes by the Fe 2+ ascorbate system [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The antioxidative activity of carnosine and 16 related compounds, both synthetic and natural, has been determined [ 15 18 ]. Antioxidative effects were estimated by the ability of the dipeptides to prevent MDA accumulation over the course of lipid peroxidation (LPO) induced in rabbit sarcoplasmic reticulum membranes by the Fe 2+ ascorbate system [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidative activity of carnosine and 16 related compounds, both synthetic and natural, has been determined [ 15 18 ]. Antioxidative effects were estimated by the ability of the dipeptides to prevent MDA accumulation over the course of lipid peroxidation (LPO) induced in rabbit sarcoplasmic reticulum membranes by the Fe 2+ ascorbate system [ 18 ]. It was found that an antioxidative effect comparable to that of carnosine was exerted by water- soluble (cyclo-L-histidyl-L-proline) and alcohol-soluble (cyclo-L-histidyl-L-phenylalanine) dipeptides, as well as by the histidine-free cyclodipeptides (cyclo-L-tyrosyl-L-proline) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations